2022
DOI: 10.1021/acsomega.2c02977
|View full text |Cite
|
Sign up to set email alerts
|

PpIX/IR-820 Dual-Modal Therapeutic Agents for Enhanced PDT/PTT Synergistic Therapy in Cervical Cancer

Abstract: High treatment accuracy is the key to efficient cancer treatment. Photodynamic therapy (PDT) and photothermal therapy (PTT) are two kinds of popular, precise treatment methods. The combination of photodynamic and photothermal therapy (PDT/PTT) can greatly enhance the precise therapeutic efficacy. In this work, protoporphyrin IX (PpIX) was selected as the PDT agent (photosensitizer), and new indocyanine green (IR-820) was selected as the PTT agent. Further, the two kinds of theranostic agents were encapsulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…We measured the absorption spectrum of Ce6 and MB using the UV-2700 ultraviolet spectrograph at 665 nm. The concentrations of Ce6 and MB in Ce6-MB@Lips were acquired using the standard curve method and calculated by using the following formulas: 46,47 where the W Ce6/MB is the quantity of Ce6 or MB in the Ce6-MB@Lips, W Ce6-MB@Lips is the weight of the Ce6-MB@Lips, and W T was the total weight of the Ce6 or MB added.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We measured the absorption spectrum of Ce6 and MB using the UV-2700 ultraviolet spectrograph at 665 nm. The concentrations of Ce6 and MB in Ce6-MB@Lips were acquired using the standard curve method and calculated by using the following formulas: 46,47 where the W Ce6/MB is the quantity of Ce6 or MB in the Ce6-MB@Lips, W Ce6-MB@Lips is the weight of the Ce6-MB@Lips, and W T was the total weight of the Ce6 or MB added.…”
Section: Methodsmentioning
confidence: 99%
“…We measured the absorption spectrum of Ce6 and MB using the UV-2700 ultraviolet spectrograph at 665 nm. The concentrations of Ce6 and MB in Ce6-MB@Lips were acquired using the standard curve method and calculated by using the following formulas: 46,47 DLC ð%Þ ¼…”
Section: Release Rate Drug Loading and Entrapment Efficiencymentioning
confidence: 99%
“…Popular precision treatment modalities include PDT and PTT. Combining PDT/PTT can significantly increase the effectiveness of the treatment [4]. As of now, materials can be employed to construct a single NIR-II light-induced nanotherapy, and acoustic dynamic therapy (SDT) collaborative phototherapy can completely eradicate tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Liu's group 4 explored the graphene oxide (GO) platform, which was functionalized with poly(ethylene glycol) and burdened with photosensitizer chlorin e6 (Ce6), for cancer combination therapy improving the efficacy of PDT. Yan et al 11 reported the PpIX-IR-820@Lipo nanoparticles (NPs) which could kill cancer cells under 793 nm (PTT) and 450 nm (PDT) laser irradiation. However, these reported materials always demand two individual laser sources because their maximum absorption spectra usually do not overlap, causing undesirable practical operation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The heat generated by graphene under laser irradiation can promote the absorption of Ce6 by cells, thus improving the efficacy of PDT. Yan et al reported the PpIX-IR-820@Lipo nanoparticles (NPs) which could kill cancer cells under 793 nm (PTT) and 450 nm (PDT) laser irradiation. However, these reported materials always demand two individual laser sources because their maximum absorption spectra usually do not overlap, causing undesirable practical operation. At present, studies have been developed in a single-wavelength near-infrared (NIR) or visible laser-induced nanosystem with a double-mode of PTT/PDT.…”
Section: Introductionmentioning
confidence: 99%